Strategi Pengemasan dan Pelabelan Produk Jajanan Jadul di Kelurahan Siwalan Kecamatan Gayamsari Semarang - Rita Meiriyanti; C. Tri Widiastuti; Rahmatya Widyaswati (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Businessman of old snack in Thematic Village, Siwalan Village, their marketing is still very limited and traditionally managed. Business actors also didn’t have proper product packaging and labeling. The aim of the Community Service Program is businessman of old snack able to implement packaging and labeling strategies in developing their products and spreading their market. This dedication activity is carried out with marketing management counseling methods, assistance in making packaging and labeling. The results of this activity are the businessman mastery of the packaging and labeling strategy and can apply simply online based marketing. Businessman of old snack are very enthusiastic to participate in this community service